Collecting in the Northern Andean Páramo revealed purple iridescent pygmy moths of the little known Andean endemic Brachinepticula (Nepticulidae) - Stonis, Jonas R.; Remeikis, Andrius; Dobrynina, Viktorija; Mey, Wolfram (Zootaxa, 2023)
This paper describes two new species of Brachinepticula Stonis & Diškus: B. melania Remeikis, Mey & Stonis, sp. nov. and B. colombica Remeikis, Mey & Stonis, sp. nov. Both the new species were collected in the Northern Andean Páramo (Cundinamarca, Colombia). Since the specimens were caught at night-time with a light trap, the host plants remain unknown. The examination of the morphology of the male genitalia of B. melania and female genitalia of B. colombica revealed a highly distinctive new taxa of pygmy moths and broadened our knowledge of the morphology and distribution of the recently described endemic genus Brachinepticula Diškus & Stonis. The examination of the new findings also allowed us updating the diagnosis of Brachinepticula. The new species were illustrated with photographs of the genitalia, adults, and habitats.